Li-Ag-X and Li-Mg-X series solid-state electrolytes
Patent Information
- Application Number
- CN202611090550.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-09
AI Technical Summary
主要原因在于,固态电解质成分空间极其庞大,固态电解质晶体结构复杂,分子动力学等评估Li离子扩散系数的工具耗时耗力
[0015]本发明提供一种计算机可存储介质,所述计算机可存储介质用于执行如上述技术方案所述的三元碱金属固态电解质的筛选方法。
Smart Images

Figure CN122889128A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials science and technology, specifically relating to Li-Ag-X and Li-Mg-X series solid electrolytes. Background Technology
[0002] With the rapid development of portable electronic devices and electric vehicles, the demand for portable energy storage devices is becoming increasingly urgent. Currently, lithium-ion batteries are the mainstream portable energy storage devices, but they face problems such as low capacity and poor range. Next-generation lithium metal batteries, especially lithium-sulfur and lithium-oxygen batteries equipped with sulfur and oxygen cathodes, have largely solved the problem of low capacity, but they still face the safety issues of flammable liquid electrolytes. All-solid-state lithium metal batteries use solid electrolytes instead of liquid electrolytes, which greatly solves this safety hazard. However, due to the nature of their physical state, the Li-ion diffusion coefficient of solid electrolytes is naturally weaker than that of liquid electrolytes. Therefore, the discovery of new solid electrolytes with high Li-ion diffusion performance is urgent. Currently, researchers mainly modify known solid electrolyte systems with high Li-ion diffusion coefficients (such as Li-Ge-PS systems, Li-PS-Cl systems, and Li-La-Zr-O systems).
[0003] However, there are not many known solid-state electrolyte systems with high Li ion diffusion coefficients, and developing new systems is another key path to improving the performance of solid-state electrolytes. Unfortunately, currently, there are no better solutions for developing solid-state electrolyte systems besides experimental trial and error. The main reason is that the compositional space of solid-state electrolytes is extremely large, their crystal structures are complex, and tools such as molecular dynamics for evaluating Li ion diffusion coefficients are time-consuming and labor-intensive.
[0004] While structural prediction methods are quite mature, they still face challenges such as complex operation and huge computational demands, hindering the development of novel solid-state electrolyte systems. Summary of the Invention
[0005] The purpose of this invention is to provide a screening method for ternary alkali metal solid electrolytes. The screening method provided by this invention has yielded solid electrolyte materials with extremely low Li ion diffusion barriers in both Li-Ag-X and Li-Mg-X ternary systems. The screening method provided by this invention will be of great significance for the development of novel solid electrolyte systems.
[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for screening ternary alkali metal solid electrolytes, comprising the following steps: (1) Determine the oxidation states of the three elements in the ternary alkali metal solid electrolyte based on their electronegativity, and determine the two binary compounds that constitute the ternary alkali metal solid electrolyte based on their oxidation states. (2) Based on the molar percentage of any binary compound in step (1) from low to high or from high to low, use the exhaustive method to obtain a series of ternary compound components that can be formed by the three elements in the ternary alkali metal solid electrolyte; (3) The crystal structure prediction method is used to predict the crystal structure of the 1-cell, 2-cell and 4-cell of a series of ternary compound components in step (2), and the predicted structure with the lowest energy among the three cell types is taken as the predicted crystal structure of a series of ternary compound components. (4) Calculate the superconvex hull energy of the predicted crystal structure of a series of ternary compound components obtained in step (3), and screen to obtain the thermodynamically stable predicted crystal structure. (5) Perform electrochemical window analysis on the thermodynamically stable predicted crystal structure obtained in step (4) to screen out electrochemically stable ternary alkali metal solid electrolyte materials. (6) The electrochemically stable ternary alkali metal solid electrolyte material obtained in step (5) is subjected to alkali metal diffusion performance test to obtain the diffusion barrier of alkali metal, and ternary alkali metal solid electrolyte with low diffusion barrier is screened; the diffusion performance includes vacancy diffusion and interstitial diffusion; the diffusion barrier includes vacancy diffusion barrier and interstitial diffusion barrier; the diffusion performance test includes constructing a damped elastic band to simulate the initial path, and then using the damped elastic band method to evaluate the vacancy diffusion barrier and interstitial diffusion barrier.
[0007] Preferably, in step (1), when the electronegativity of an element is ≥2.4, its oxidation state is negative; when the electronegativity of an element is <2.4, its oxidation state is positive.
[0008] Preferably, in step (4), when the superconvex hull energy per atom is <50 meV, a thermodynamically stable predicted crystal structure is obtained by screening.
[0009] Preferably, in step (3), the crystal structure prediction method is performed using crystal structure prediction software, which is CALYPSO; in step (5), the electrochemical window analysis is performed using the Pymatgen Python library; in step (6), the initial path of the damping elastic band simulation is constructed using the IDPP method, and the damping elastic band method uses VASP software as the computational simulation software.
[0010] Preferably, the vacancy diffusion test includes the following steps: using crystal symmetry analysis, the number of equivalent alkali metal atoms in the unit cell of the electrochemically stable ternary alkali metal solid electrolyte material obtained in step (5) is calculated to obtain the number of vacancies in the unit cell; the vacancy formation energy of each type of vacancy is calculated, and the vacancy with the lowest vacancy formation energy is selected as the most stable vacancy in the unit cell. Taking the most stable vacancy in the unit cell as the center, the distance from it to each equivalent alkali metal atom is calculated. Using 5 Å as the threshold, diffusion paths with a distance ≥ 5 Å are excluded. For diffusion paths with a distance less than 5 Å, it is determined whether they can diffuse over long distances. For paths that can diffuse over long distances and have a distance less than 5 Å, a damped elastic band is constructed to simulate the initial path. Then, the damped elastic band method is used to evaluate the vacancy diffusion energy barrier.
[0011] Preferably, the interstitial diffusion test includes the following steps: a three-dimensional grid is constructed in the cell of the electrochemically stable ternary alkali metal solid electrolyte material obtained in step (5), and alkali metal test atoms are placed at each grid point. When the distance between the alkali metal test atoms and the original atoms in the crystal structure of the electrochemically stable ternary alkali metal solid electrolyte material is greater than 1.5 Å, the potential position of the alkali metal interstitial atom is obtained; using the crystal symmetry analysis method, the equivalent alkali metal interstitial atoms at the potential positions of the alkali metal interstitial atoms are grouped, and only one is retained in each group as a representative alkali metal interstitial atom; the interstitial formation energy of the representative alkali metal interstitial atom is calculated, and the one with the lowest energy is the most stable alkali metal interstitial atom. The most stable alkali metal interstitial atom is taken as the initial position, and the equivalent adjacent site in the unobstructed direction in the crystal is taken as the final position to form a potential diffusion path. A damped elastic band is constructed to simulate the initial path, and then the damped elastic band method is used to evaluate the interstitial diffusion energy barrier.
[0012] Preferably, the elemental composition of the ternary alkali metal solid electrolyte includes Li-Ag-X or Li-Mg-X, wherein X is O, S or Cl.
[0013] Preferably, the ternary alkali metal solid electrolytes obtained through screening include LiAg5S3, LiAg3S2, Li2Ag4S3, LiAgS, Li4Ag2S3, Li3AgS2, Li5AgS3, LiAg5O3, LiAg3O2, Li2Ag4O3, LiAgO, Li4Ag2O3, Li3AgO2, Li5AgO3, Li2MgS2, Li4MgS3, Li6MgS4, Li8MgS5, and Li 10 MgS6.
[0014] This invention provides a screening system for ternary alkali metal solid electrolytes, comprising: The dimensionality reduction module for the composition space of ternary alkali metal solid electrolytes is used to determine the two binary compounds that constitute the ternary solid electrolyte based on the electronegativity of the three elements that make up the ternary solid electrolyte. The module uses an exhaustive method to generate a series of candidate components of ternary solid electrolytes with different compositions that can be formed by the three elements in the ternary alkali metal solid electrolyte from the two binary compounds, thereby achieving dimensionality reduction of the composition space. An automated structure prediction module is connected to the ternary alkali metal solid electrolyte component spatial dimensionality reduction module to receive each ternary solid electrolyte candidate component, and to perform crystal structure prediction and total crystal energy calculation for each candidate component at 1x, 2x, and 4x unit cells, and to screen out the optimal crystal structure with the lowest energy for each candidate component. The crystal performance screening module is connected to the automated structure prediction module to receive the optimal crystal structure of each candidate component, screen out thermodynamically stable candidate materials with a superconvex hull energy per atom <50 meV through phase diagram analysis, and then perform electrochemical window analysis on the thermodynamically stable candidate materials to screen out electrochemically stable candidate materials. An alkali metal ion diffusion performance measurement module is connected to the crystal performance screening module to receive electrochemically stable candidate materials, test the alkali metal vacancy diffusion performance and alkali metal interstitial diffusion performance of the electrochemically stable candidate materials, and screen out ternary alkali metal solid electrolytes with low diffusion barriers based on the diffusion energy barrier of alkali metals.
[0015] The present invention provides a computer-storable medium for performing the screening method for ternary alkali metal solid electrolytes as described in the above technical solution.
[0016] This invention provides a method and system for screening ternary alkali metal solid electrolytes. The invention reveals that elements in solid electrolytes often exhibit their common valence states, manifesting as ionic or covalent crystals. Furthermore, the gain or loss of electrons (positive or negative valence) during elemental combination primarily depends on their electronegativity. These facts assign a unique valence state to each element constituting a solid electrolyte. Based on this, although solid electrolytes often contain numerous elements, the fixed valence state essentially reduces the degree of freedom in the compositional space. For example, the composition of a ternary alkali metal solid electrolyte originally has two degrees of freedom, meaning the content of two elements can vary. However, by fixing the valence state, this degree of freedom is reduced from two to one. It can be considered that the ternary alkali metal solid electrolyte is composed of two binary compounds, thus only the content of one compound can vary, thereby significantly reducing the compositional space of the solid electrolyte. This invention proposes a systematic screening method and system capable of systematically studying the chemical composition, crystal structure, and alkali metal (e.g., Li) ion diffusion properties of ternary alkali metal solid electrolytes, and this has been achieved in both Li-Ag-X and Li-Mg-X systems. Currently, existing technologies mainly improve the performance of known solid electrolyte materials with high Li ion diffusion coefficients by modifying them. However, an effective method is lacking for the development of novel solid electrolyte systems. Compared with existing technologies, this invention offers the following advantages: Based on the fact that elements in solid electrolytes often appear in their common valence states, this invention reduces the degree of freedom of the ternary composition space to one dimension, greatly narrowing the research scope of novel solid electrolytes. Based on the reduced composition space, this invention constructs an automated process for crystal structure prediction, achieving the analysis of the ground-state crystal structure. Finally, this invention proposes a method for systematically studying the diffusion barrier of ternary alkali metal solid electrolyte materials. Based on the more efficient damped elastic band method, it achieves accurate judgment of the diffusion performance of alkali metal ions (e.g., Li ions). Based on the screening method provided by this invention, solid electrolyte materials with extremely low Li ion diffusion barriers have been discovered in both the Li-Ag-X and Li-Mg-X ternary systems. In summary, the screening method provided by this invention has a complete technical route and clear theoretical significance, achieving a major leap from trial and error to theoretically guided exploration. This invention provides important theoretical tools and practical materials for the exploration of solid electrolyte systems in all-solid-state batteries. Attached Figure Description
[0017] Figure 1 The predicted crystal structure of the Li-Ag-S ternary solid electrolyte system; Figure 2 The Li diffusion performance of the Li-Ag-S ternary solid electrolyte; Figure 3 The predicted crystal structure of the Li-Ag-O ternary solid electrolyte system; Figure 4 The Li diffusion performance of the Li-Ag-O ternary solid electrolyte; Figure 5 The predicted crystal structure of the Li-Mg-S ternary solid electrolyte system; Figure 6 The Li diffusion performance of the Li-Mg-S ternary solid electrolyte; Figure 7 The results are the electronegativity analysis of elements in solid electrolytes; Figure 8 This is a schematic diagram of the long-range diffusion pathway in Li3PO4 material. Figure 9 This is a schematic diagram of the pathways in Li3PO4 materials that cannot diffuse over long distances. Figure 10 This is a schematic diagram of a Li3PO4 material with a spacing of 3.01 angstroms between two adjacent Li particles along the diffusion path. Figure 11 This is a schematic diagram of the structure of Li3PO4 material with a spacing of 5.70 angstroms between two adjacent Li particles in the diffusion path. Detailed Implementation
[0018] This invention provides a method for screening ternary alkali metal solid electrolytes, comprising the following steps: (1) Determine the oxidation states of the three elements in the ternary alkali metal solid electrolyte based on their electronegativity, and determine the two binary compounds that constitute the ternary alkali metal solid electrolyte based on their oxidation states. (2) Based on the molar percentage of any binary compound in step (1) from low to high or from high to low, use the exhaustive method to obtain a series of ternary compound components that can be formed by the three elements in the ternary alkali metal solid electrolyte; (3) The crystal structure prediction method is used to predict the crystal structure of the 1-cell, 2-cell and 4-cell of a series of ternary compound components in step (2), and the predicted structure with the lowest energy among the three cell types is taken as the predicted crystal structure of a series of ternary compound components. (4) Calculate the superconvex hull energy of the predicted crystal structure of a series of ternary compound components obtained in step (3), and screen to obtain the thermodynamically stable predicted crystal structure. (5) Perform electrochemical window analysis on the thermodynamically stable predicted crystal structure obtained in step (4) to screen out electrochemically stable ternary alkali metal solid electrolyte materials. (6) The electrochemically stable ternary alkali metal solid electrolyte material obtained in step (5) is subjected to alkali metal diffusion performance test to obtain the diffusion barrier of alkali metal, and ternary alkali metal solid electrolyte with low diffusion barrier is screened; the diffusion performance includes vacancy diffusion and interstitial diffusion; the diffusion barrier includes vacancy diffusion barrier and interstitial diffusion barrier; the diffusion performance test includes constructing a damped elastic band to simulate the initial path, and then using the damped elastic band method to evaluate the vacancy diffusion barrier and interstitial diffusion barrier.
[0019] In this invention, unless otherwise specified, all raw materials / components used in the preparation are commercially available products well known to those skilled in the art.
[0020] In this invention, the alkali metal in the ternary alkali metal solid electrolyte can be Li. The ternary alkali metal solid electrolyte preferably includes Li-Ag-X or Li-Mg-X, wherein X is preferably O, S, or C.
[0021] This invention specifies three elements of a ternary alkali metal solid electrolyte, determines the valence of each element in the ternary alkali metal solid electrolyte based on the electronegativity of each element, and determines two binary compounds constituting the ternary alkali metal solid electrolyte based on the valence.
[0022] This invention specifies three elements for a ternary alkali metal solid electrolyte, such as Li-Ag-O. In this invention, when the electronegativity of an element is ≥2.40, its valence is negative (negative valence is commonly used; for example, O should have a valence of -2, and Cl should have a valence of -1); when the electronegativity of an element is <2.40, its valence is positive (positive valence is commonly used).
[0023] Through statistical analysis of a large number of solid electrolytes, this invention has discovered that the valence of an element in a solid electrolyte is directly related to its electronegativity. Figure 7 This invention analyzes dozens of existing solid electrolytes and discovers... Figure 7 The solid electrolytes shown all meet the following criteria: with an electronegativity threshold of 2.40, elements with electronegativity above the threshold behave as anions, and elements with electronegativity below the threshold behave as cations. Building upon this, the present invention uses an electronegativity threshold of 2.40, where elements with electronegativity above the threshold behave as common anions, and elements with electronegativity below the threshold behave as common cations.
[0024] In this invention, an electronegativity of 2.40 is used as a threshold. When the electronegativity of an element is greater than 2.40, its atomic nucleus has a strong attraction to electrons, and it readily gains electrons in solid electrolytes (becoming an anion), with its most common negative valence. When the electronegativity of an element is less than 2.40, its atomic nucleus has a weak attraction to electrons, and it readily loses electrons in solid electrolytes (becoming a cation), with its most common positive valence. Taking the Li-Ag-O system as an example, where Li has an electronegativity of 0.98, in a solid electrolyte, it should exhibit the following behavior: Li + Its oxidation state is +1; Ag has an electronegativity of 1.93, and in a solid electrolyte, it should exhibit the characteristic of Ag > 1.93. + The oxidation state of O is +1; the electronegativity of O is 3.44, and in a solid electrolyte, it should exhibit the characteristic of O being the most reactive element. 2- Its oxidation state is -2.
[0025] This invention, based on determining the valence of each element in a ternary alkali metal solid electrolyte according to its electronegativity, further identifies two binary compounds constituting the ternary alkali metal solid electrolyte, thereby achieving a reduction in the dimensionality of the composition space. Taking the Li-Ag-O system as an example, without any restrictions, determining a component in the ternary Li-Ag-O system requires two degrees of freedom; for example, specifying the molar percentage of Li and Ag can determine a component (molar percentage of O = 1 - molar percentage of Li - molar percentage of Ag). However, in the ternary Li-Ag-O solid electrolyte system, since this invention determines the valence of all three elements, it essentially reduces the two degrees of freedom required to determine the component to one, meaning that specifying the molar percentage of Li₂O can determine a component (molar percentage of Ag₂O = 1 - molar percentage of Li₂O).
[0026] After identifying two binary compounds, this invention uses an exhaustive method to obtain a series of ternary compound components that can be formed by the three elements in a ternary alkali metal solid electrolyte, based on the molar percentage of any binary compound from low to high or from high to low.
[0027] This invention, by identifying two binary compounds, yields a series of ternary compound compositions, significantly narrowing the possible compositional space and reducing the degree of freedom in compositional space from two dimensions to one. Since ternary alkali metal solid electrolytes necessarily contain two anionic elements and one cationic element, or two cationic elements and one anionic element, two compounds can be combined to form them. Thus, the composition of ternary alkali metal solid electrolytes is transformed from being described by three elements to being described by two compounds.
[0028] This invention achieves a reduction in the dimensionality of the composition space of a ternary alkali metal solid electrolyte by specifying three elements, determining the valences of these three elements, and further identifying two binary compounds constituting the ternary alkali metal solid electrolyte based on the obtained valences. In summary, the composition space of a ternary alkali metal solid electrolyte can be fully described by only one variable. Taking Li-Ag-O as an example, the molar percentage of Li2O can completely describe the composition space of the ternary Li-Ag-O solid electrolyte. For example, when the molar percentage of Li2O is 16.67%, the corresponding solid electrolyte composition is LiAg5O3; when the molar percentage of Li2O is 25.00%, the corresponding solid electrolyte composition is LiAg3O2; and so on.
[0029] This invention uses a spatial dimension reduction method for ternary alkali metal solid electrolyte components to obtain a series of ternary compound components. Taking the Li-Ag-O system as an example, as the molar percentage of Li2O increases, the following ternary Li-Ag-O solid electrolyte components can be obtained: LiAg5O3, LiAg3O2, Li2Ag4O3, LiAgO, Li4Ag2O3, Li3AgO2, and Li5AgO3.
[0030] After obtaining a series of ternary compound components, the present invention uses a crystal structure prediction method to predict the crystal structure of the 1-cell, 2-cell, and 4-cell units of the series of ternary compound components, and takes the predicted structure with the lowest energy per atom among the three unit cells as the predicted crystal structure of the series of ternary compound components.
[0031] In this invention, the crystal structure prediction method is preferably performed using crystal structure prediction software, and the crystal structure prediction software is preferably CALYPSO (a domestic software).
[0032] This invention uses CALYPSO software for crystal structure prediction because the method of crystal structure prediction is automated. It only requires providing the material composition and deploying it on a computing cluster to automatically predict the ground state crystal structure corresponding to that composition, which has the advantage of end-to-end.
[0033] This invention selects appropriate structure prediction algorithms and crystal total energy calculation algorithms to predict the crystal structure of a series of ternary compound compositions at 1-cell, 2-cell, and 4-cell values. The predicted structure with the lowest energy per atom per cell is taken as the crystal structure of that composition. Taking the LiAg5O3 composition of the Li-Ag-O system as an example, the crystal structure prediction should be performed on LiAg5O3 and Li2Ag... 10 O6, Li4Ag 20 O 12Crystal structure prediction was performed using three chemical formulas, yielding three predicted crystal structures. Taking E(LiAg5O3) and 1 / 2 E(Li2Ag) as examples... 10 O6), 1 / 4 E(Li4Ag) 20 O 12 The crystal structure corresponding to the lowest value in the () is taken as the crystal structure of LiAg5O3.
[0034] After obtaining the predicted crystal structures of a series of ternary compound components, this invention calculates the energy above hull of the predicted crystal structures of a series of ternary compound components and screens out the thermodynamically stable predicted crystal structures.
[0035] In this invention, when the energy above hull per atom is preferably <50 meV, a thermodynamically stable predicted crystal structure is obtained through screening. This invention performs phase diagram analysis on the predicted crystal structures of a series of ternary compound compositions. Those with an energy above hull per atom <50 meV have a very high probability of being synthesized experimentally (i.e., the experimental synthesis conditions are met), and are thus considered as thermodynamically stable candidate materials.
[0036] After obtaining the thermodynamically stable predicted crystal structure, the present invention performs electrochemical window analysis on the obtained thermodynamically stable predicted crystal structure to screen and obtain electrochemically stable ternary alkali metal solid electrolyte materials.
[0037] In this invention, the electrochemical window analysis is preferably performed using the Pymatgen Python library; that is, this invention uses the Pymatgen Python library for phase diagram analysis and electrochemical window analysis. This invention performs electrochemical window analysis on the thermodynamically stable predicted crystal structures obtained through screening. Electrochemical windows that offer advantages over existing solid electrolytes can be considered as electrochemically stable candidate materials.
[0038] After obtaining electrochemically stable ternary alkali metal solid electrolyte materials, this invention conducts alkali metal diffusion performance tests on these materials to determine the diffusion barriers of the alkali metals and screens for ternary alkali metal solid electrolytes with low diffusion barriers. The diffusion performance includes vacancy diffusion and interstitial diffusion; the diffusion barriers include vacancy diffusion barriers and interstitial diffusion barriers. The diffusion performance test involves constructing a damped elastic band to simulate the initial path, and then using the damped elastic band method to evaluate the vacancy diffusion barrier and the interstitial diffusion barrier. This invention studies in detail the alkali metal (e.g., Li) vacancy diffusion and interstitial diffusion performance of electrochemically stable ternary alkali metal solid electrolyte materials, thereby systematically evaluating the alkali metal (e.g., Li) diffusion performance of candidate materials (e.g., electrochemically stable ternary alkali metal solid electrolyte materials). This invention uses the damped elastic band method to study the alkali metal (e.g., Li) diffusion barrier, where the alkali metal (e.g., Li) diffusion path should start from a stable site, diffuse to an equivalent stable site, and should have long-range diffusion capability.
[0039] In this invention, the initial path of the damped elastic band simulation is preferably constructed using the IDPP method. The damped elastic band method preferably uses VASP software as the computational simulation software. This invention can comprehensively measure the vacancy diffusion and gap diffusion energy barriers of a substance, greatly reducing the subjectivity in energy barrier calculations, thereby more accurately measuring the Li-ion diffusion performance of a material.
[0040] In this invention, the vacancy diffusion test preferably includes the following steps: using crystal symmetry analysis, the number of equivalent alkali metal atoms in the unit cell of the electrochemically stable ternary alkali metal solid electrolyte material is calculated to obtain the number of vacancies in the unit cell; the vacancy formation energy of each type of vacancy is calculated, and the vacancy with the lowest vacancy formation energy is selected as the most stable vacancy in the unit cell; taking the most stable vacancy in the unit cell as the center, the distance from it to each equivalent alkali metal atom is calculated; using 5 Å as a threshold, diffusion paths with a distance ≥ 5 Å are excluded; for diffusion paths with a distance less than 5 Å, it is determined whether they can diffuse over a long distance; for paths that can diffuse over a long distance and have a distance less than 5 Å, a damped elastic band is constructed to simulate the initial path, and then the damped elastic band method is used to evaluate the vacancy diffusion energy barrier.
[0041] In this invention, the vacancy diffusion test specifically includes the following steps: First, using crystal symmetry analysis, the number of equivalent alkali metals (e.g., Li) in the unit cell is calculated. Assuming there are N types of equivalent alkali metals (e.g., Li) in the unit cell, this means there are N ways vacancies can form within the unit cell. The vacancy formation energy of these N types of vacancies is calculated, and the vacancy formation energy with the lowest energy is the most stable vacancy formation mode. Alkali metal (e.g., Li) vacancy diffusion should occur between alkali metal (e.g., Li) atoms and these alkali metal (e.g., Li) vacancies. Using these alkali metal (e.g., Li) vacancies as the center, the distance from them to each equivalent alkali metal (e.g., Li) atom is calculated and arranged in ascending order of distance. Since there is a certain positive correlation between the alkali metal (e.g., Li) diffusion barrier and the alkali metal (e.g., Li) diffusion distance, this invention sets a maximum threshold value (e.g., 5 Å) for the distance. Alkali metal (e.g., Li) vacancies and alkali metal (e.g., Li) atoms whose distances are within this threshold and which can diffuse over long distances are considered potential alkali metal (e.g., Li) vacancy diffusion paths. By considering all potential alkali metal (e.g., Li) vacancy diffusion pathways, the vacancy diffusion performance of alkali metals (e.g., Li) can be systematically measured.
[0042] In this invention, Li3PO4 is used as an example, such as Figure 8 The aforementioned vacancy diffusion path, Figure 8 In the diagram, the green sphere represents Li, the red sphere represents O, and the purple sphere represents P. Li can diffuse indefinitely along the directions marked in the diagram; this is the vacancy diffusion path that enables long-range diffusion, such as... Figure 9 Another vacancy diffusion path is shown. Figure 9 Every three Li atoms, a P atom will appear, blocking the diffusion of Li. Therefore, this path cannot achieve long-range diffusion. In summary, to determine whether a path can achieve long-range diffusion, we need to see if the alkali metal (such as Li) can diffuse indefinitely along this path without any obstruction.
[0043] In this invention, taking Li3PO4 as an example, the following are the pathways through which long-range diffusion can be achieved in Li3PO4: Figure 10 The distance between two adjacent Li values on the path is shown to be 3.01 Å. Figure 11The distance between two adjacent Li atoms in the diffusion path is shown to be 5.70 Å. Empirically, the larger the distance between two adjacent Li atoms, the higher the diffusion barrier and the greater the difficulty of diffusion. Therefore, this invention sets a threshold (5 Å). When the distance between two adjacent Li atoms in a long-range diffusion path exceeds this threshold, the diffusion barrier of that path is likely very high and has no practical value, so this invention does not evaluate that path. This invention uses a 5 Å threshold to filter long-range diffusion paths. A path must first satisfy the requirement of being able to diffuse over long distances, and secondly, the distance between adjacent Li atoms must be less than the threshold (5 Å) to be considered a path with evaluation value. Figure 10 The path in the middle has evaluation value, and Figure 11 Although the path in the middle can also spread over long distances, the distance between adjacent Li is too large, making it difficult to predict the spread process, so it is directly excluded.
[0044] In this invention, the interstitial diffusion test preferably includes the following steps: constructing a three-dimensional grid in the unit cell of an electrochemically stable ternary alkali metal solid electrolyte material, placing a test atom at each grid point, and if the distance between the test atom and the original atoms in the crystal structure of the electrochemically stable ternary alkali metal solid electrolyte material is greater than 1.5 Å, the potential positions of the alkali metal interstitial atoms are obtained; using crystal symmetry analysis, grouping the equivalent alkali metal interstitial atoms at the potential positions of the alkali metal interstitial atoms, retaining only one in each group as a representative alkali metal interstitial atom; calculating the interstitial formation energy of the representative alkali metal interstitial atom, the one with the lowest energy is the most stable alkali metal interstitial atom, using the most stable alkali metal interstitial atom as the initial position, selecting an unobstructed direction in the crystal, and using the equivalent adjacent sites in this direction as the final positions to form a potential diffusion path, constructing a damped elastic band to simulate the initial path, and then using the damped elastic band method to evaluate the interstitial diffusion energy barrier.
[0045] In this invention, the interstitial diffusion test aims to determine the most stable interstitial alkali metal (e.g., Li) atom formation mode. To this end, a three-dimensional grid is constructed within the unit cell, and a judgment is made at each grid point. If the distance from this grid point to the original interatomic spacing in the unit cell is greater than a certain threshold (e.g., 1.5 Å), then this grid point is a potential interstitial atom formation site for alkali metal (e.g., Li). Since this method yields too many potential Li interstitial atom formation sites, a crystal symmetry analysis method is further employed to divide these potential sites into multiple equivalent groups. Only one potential site is ultimately retained in each group, thus greatly reducing the number of potential sites without compromising generality. Li atoms are placed at these potential sites to construct an alkali metal (e.g., Li) interstitial model, and the structure is optimized. After optimization, alkali metal (e.g., Li) interstitial models with similar energies likely correspond to the same alkali metal (e.g., Li) interstitial sites; one of these is selected. Finally, the lowest energy among the selected alkali metal (e.g., Li) interstitial sites is identified as the most stable alkali metal (e.g., Li) interstitial formation site. Starting from this position, an unobstructed direction in the crystal is selected, and equivalent adjacent sites in this direction are identified, thus forming a potential diffusion path. By considering all potential diffusion paths, the interstitial diffusion performance of Li can be systematically evaluated.
[0046] In this invention, the ternary alkali metal solid electrolytes obtained through screening include LiAg5S3, LiAg3S2, Li2Ag4S3, LiAgS, Li4Ag2S3, Li3AgS2, Li5AgS3, LiAg5O3, LiAg3O2, Li2Ag4O3, LiAgO, Li4Ag2O3, Li3AgO2, Li5AgO3, Li2MgS2, Li4MgS3, Li6MgS4, Li8MgS5, and Li 10 MgS6.
[0047] This invention provides a screening system for ternary alkali metal solid electrolytes, comprising: The dimensionality reduction module for the composition space of ternary alkali metal solid electrolytes is used to determine the two binary compounds that constitute the ternary solid electrolyte based on the electronegativity of the three elements that make up the ternary solid electrolyte. The module uses an exhaustive method to generate a series of candidate components of ternary solid electrolytes with different compositions that can be formed by the three elements in the ternary alkali metal solid electrolyte from the two binary compounds, thereby achieving dimensionality reduction of the composition space. An automated structure prediction module is connected to the ternary alkali metal solid electrolyte component spatial dimensionality reduction module to receive each ternary solid electrolyte candidate component, and to perform crystal structure prediction and total crystal energy calculation for each candidate component at 1x, 2x, and 4x unit cells, and to screen out the optimal crystal structure with the lowest energy for each candidate component. The crystal performance screening module is connected to the automated structure prediction module to receive the optimal crystal structure of each candidate component, screen out thermodynamically stable candidate materials with a superconvex hull energy per atom <50 meV through phase diagram analysis, and then perform electrochemical window analysis on the thermodynamically stable candidate materials to screen out electrochemically stable candidate materials. An alkali metal ion diffusion performance measurement module is connected to the crystal performance screening module to receive electrochemically stable candidate materials, test the alkali metal vacancy diffusion performance and alkali metal interstitial diffusion performance of the electrochemically stable candidate materials, and screen out ternary alkali metal solid electrolytes with low diffusion barriers based on the diffusion energy barrier of alkali metals.
[0048] The present invention provides a computer-storable medium for performing the screening method for ternary alkali metal solid electrolytes as described in the above technical solution.
[0049] To further illustrate the present invention, the technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0050] Example 1: This embodiment provides a prediction of the crystal structure and a study of the Li diffusion performance of a Li-Ag-S ternary solid-state electrolyte system: First, determine the oxidation states of Li, Ag, and S in the solid electrolyte. Since the electronegativity of Li, Ag, and S are 0.98, 1.93, and 2.58, respectively, and the electronegativity of Li and Ag is less than 2.40, while that of S is greater than 2.40, Li and Ag are the common cations, i.e., Li2 and Ag are the common cations. + and Ag + S is a common anion, namely S 2- Next, all the above ternary compounds can be described as mixtures of Li2S and Ag2S. From left to right, the content of Li2S gradually increases and the content of Ag2S gradually decreases. Using an exhaustive method, the composition of the ternary compounds that can be formed by the above three ions is obtained, namely LiAg5S3, LiAg3S2, Li2Ag4S3, LiAgS, Li4Ag2S3, Li3AgS2, and Li5AgS3 (7 materials), which is consistent with the composition space dimensionality reduction (reduced from two degrees of freedom to one degree of freedom).
[0051] After the composition of the Li-Ag-S ternary solid-state electrolyte system was determined, crystal structure prediction methods were used to predict the crystal structures of the above seven materials at 1x, 2x, and 4x unit cells. The lowest energy among the three was taken as the predicted crystal structure. The results are as follows: Figure 1 As shown. Figure 1The predicted crystal structure of the Li-Ag-S ternary solid-state electrolyte system. Figure 1 The leftmost part is the Ag2S crystal structure, and the rightmost part is the Li2S crystal structure. From left to right, it is the gradual transition from Ag2S to Li2S. The gradual decrease of Ag2S content and the gradual increase of Li2S content can be clearly observed.
[0052] This embodiment calculates the Energy above hull for the seven predicted crystal structures. The calculations show that the Energy above hull for all seven predicted crystal structures is less than 50 meV / atom. Among them, LiAgS and LiAg3S2 have an Energy above hull of 0, indicating excellent thermodynamic stability.
[0053] This embodiment uses the Pymatgen Python library for phase diagram analysis and electrochemical window analysis to calculate the electrochemical windows for the seven predicted crystal structures. The calculations show that the electrochemical windows for these seven predicted crystal structures are similar to those of traditional S-based solid electrolytes (Li). 10 GeP2S 12 )quite.
[0054] This embodiment systematically studies the Li diffusion performance of the seven predicted crystal structures mentioned above. The Li diffusion performance needs to be examined from two aspects: vacancy diffusion and interstitial diffusion. For vacancy diffusion, the location of the most stable Li vacancy should first be determined. Using crystal symmetry analysis, the number of equivalent Li types in the seven predicted crystal structures is calculated. For LiAg5S3, LiAg3S2, Li2Ag4S3, LiAgS, and Li4Ag2S3, the number of equivalent Li types is 1. That is, in these crystal structures, all Li types are symmetrically equivalent, so removing any one Li type to create a vacancy will yield the most stable Li vacancy. Li3AgS2 has two types of equivalent Li; the vacancy formation energy of these two types of Li needs to be calculated, and the vacancy corresponding to the one with the lower formation energy is the most stable Li vacancy. Li5AgS3 has three types of equivalent Li; similar to Li3AgS2, the most stable Li vacancy is determined by the vacancy formation energy. After obtaining the most stable Li vacancy, the next step is to determine the Li vacancy diffusion paths that are meaningful for evaluation. For any of the predicted crystal structures mentioned above, calculate the distance between the most stable Li vacancy and the surrounding Li atoms, and arrange them in ascending order. Use 5 Å as a threshold to exclude paths with excessively large distances. For paths with distances less than 5 Å, determine whether they can diffuse over long distances, and further exclude paths that cannot diffuse over long distances. For paths that can diffuse over long distances and whose diffusion distance is less than 5 Å, use the IDPP method to construct the initial path for the damped elastic band simulation, and use VASP software as the simulation software for the damped elastic band method to evaluate the path energy barrier.
[0055] For interstitial diffusion, similarly, the location of the most stable Li interstitial atom should first be determined. To this end, a 24×24×24 three-dimensional grid was constructed in the seven predicted crystal structures mentioned above. A test atom (Li) was placed at each grid point. If the distance between the test atom and all existing atoms in the predicted crystal structure was greater than 1.5 Å, it indicated that placing the Li interstitial atom at that point would not overlap with the existing atoms, making it a potential location for the Li interstitial atom. Since there were too many potential Li interstitial atoms, and many of them were symmetrically equivalent, a crystal symmetry analysis method was used to group the equivalent Li interstitial atoms, retaining only one representative from each group. The interstitial formation energy of these representative Li interstitial atoms was calculated; the lowest energy corresponded to the most stable Li interstitial atom. Using this location as the initial position, an unobstructed direction in the crystal was selected, and the adjacent sites in this direction were used as the final positions to form potential diffusion paths. The IDPP method was used to construct the initial path for the damped elastic band simulation, and VASP software was used as the simulation software for the damped elastic band method to evaluate the path energy barrier. Figure 2 As shown. Figure 2 The Li diffusion performance of the Li-Ag-S ternary solid electrolyte in Example 1 is shown. Li3AgS2 exhibits a vacancy diffusion barrier of only 0.184 eV, while LiAgS shows an even higher barrier of only 0.058 eV. This highlights the significant potential of the Li-Ag-S ternary solid electrolyte system.
[0056] Example 2: This embodiment provides a prediction of the crystal structure and a study of the Li diffusion performance of a Li-Ag-O ternary solid-state electrolyte system: First, determine the oxidation states of Li, Ag, and O in the solid electrolyte. Since the electronegativity of Li, Ag, and O are 0.98, 1.93, and 3.44, respectively, and the electronegativity of Li and Ag is less than 2.40, while that of O is greater than 2.40, Li and Ag are the common cations, i.e., LiO. + and Ag + O is a common anion, namely O 2-Next, all the aforementioned ternary compounds can be described as mixtures of Li₂O and Ag₂O. From left to right, the content of Li₂O gradually increases, and the content of Ag₂O gradually decreases. Using an exhaustive method, the composition of the ternary compounds that can be formed by the three ions is determined: LiAg₅O₃, LiAg₃O₂, Li₂Ag₄O₃, LiAgO, Li₄Ag₂O₃, Li₃AgO₂, and Li₅AgO₃ (7 materials), which conforms to composition space dimensionality reduction (reducing from two degrees of freedom to one degree of freedom). After clarifying the composition of the Li-Ag-O ternary solid-state electrolyte system, crystal structure prediction methods were used to predict the crystal structures of the above 7 materials at 1x, 2x, and 4x unit cells. The lowest energy among the three was taken as the predicted crystal structure. The results are as follows: Figure 3 As shown. Figure 3 The predicted crystal structure of the Li-Ag-O ternary solid electrolyte system in Example 2. Figure 3 The leftmost part is the Ag2O crystal structure, and the rightmost part is the Li2O crystal structure. From left to right, it is the gradual transition from Ag2O to Li2O. It can be clearly observed that the Ag2O content gradually decreases and the Li2O content gradually increases.
[0057] This embodiment calculates the Energy above hull for the seven predicted crystal structures. The calculations show that the Energy above hull for all seven predicted crystal structures is less than 50 meV / atom, indicating their thermodynamic stability.
[0058] This embodiment uses the Pymatgen Python library for phase diagram analysis and electrochemical window analysis to calculate the electrochemical windows for the seven predicted crystal structures. The calculations show that the electrochemical windows for these seven predicted crystal structures are similar to those of the traditional O-based solid electrolyte (Li7La3Zr2O). 12 The results are comparable. It is evident that the electrochemical stability of O-based solid electrolytes is much better than that of S-based solid electrolytes.
[0059] This embodiment systematically studies the Li diffusion performance of the above seven predicted crystal structures. The Li diffusion performance needs to be examined from two aspects: vacancy diffusion and interstitial diffusion. For vacancy diffusion, the location of the most stable Li vacancy should first be determined. Using crystal symmetry analysis, the number of equivalent Li types in the above seven predicted crystal structures is calculated. The number of equivalent Li types for LiAg5O3, LiAg3O2, and LiAgO is 1, so the vacancy obtained by removing any Li atom is the most stable vacancy. The number of equivalent Li types for Li2Ag4O3, Li4Ag2O3, and Li3AgO2 is 2; and the number of equivalent Li types for Li5AgO3 is 5. Therefore, for Li2Ag4O3, Li4Ag2O3, Li3AgO2, and Li5AgO3, the location of the most stable Li vacancy needs to be determined by calculating the Li vacancy formation energy. After obtaining the most stable Li vacancy, the next step is to determine the Li vacancy diffusion path that is significant for evaluation. For any of the predicted crystal structures mentioned above, the distance between the most stable Li vacancy and its surrounding Li atoms is calculated and arranged in ascending order. Paths with excessively large distances are excluded using a 5 Å threshold. For paths with distances less than 5 Å, their long-range diffusion capability is assessed, further excluding paths that cannot diffuse over long distances. For paths capable of long-range diffusion with a diffusion distance less than 5 Å, the IDPP method is used to construct the initial path for damped elastic band simulation, and VASP software is used as the simulation software for the damped elastic band method to evaluate the path energy barrier.
[0060] For interstitial diffusion, similarly, the location of the most stable Li interstitial atom should first be determined. To this end, a 24×24×24 three-dimensional grid was constructed in the seven predicted crystal structures mentioned above. A test atom was placed at each grid point. If the distance between the test atom and all existing atoms in the predicted crystal structure was greater than 1.5 Å, it indicated that placing a Li interstitial atom at that point would not overlap with the existing atoms, making it a potential location for a Li interstitial atom. Since there were too many potential Li interstitial atoms, and many of them were symmetrically equivalent, a crystal symmetry analysis method was used to group the equivalent Li interstitial atoms, retaining only one representative from each group. The interstitial formation energy of these representative Li interstitial atoms was calculated; the lowest energy corresponded to the most stable Li interstitial atom. Using this location as the initial position, an unobstructed direction in the crystal was selected, and the adjacent sites in this direction were used as the final positions to form potential diffusion paths. The IDPP method was used to construct the initial path for damped elastic band simulation, and VASP software was used as the simulation software for the damped elastic band method to evaluate the path energy barrier. Figure 4As shown, although the vacancy diffusion and interstitial diffusion performance of the Li-Ag-O system is not as good as that of the Li-Ag-S system, O-based solid electrolytes generally have weak Li diffusion ability (even so, their diffusion ability is still better than the minimum requirement of 0.30 eV). Considering their stronger electrochemical stability compared to S-based solid electrolytes, they still have the potential to become excellent solid electrolytes.
[0061] Example 3: This embodiment provides a prediction of the crystal structure and a study of the Li diffusion performance of a Li-Mg-S ternary solid electrolyte system: First, determine the oxidation states of Li, Mg, and S in the solid electrolyte. Since the electronegativity of Li, Mg, and S are 0.98, 1.31, and 2.58, respectively, and the electronegativity of Li and Mg is less than 2.40, while that of S is greater than 2.40, Li and Mg are the most common cations, i.e., Li... + and Mg 2+ S is a common anion, namely S 2- Next, all the above ternary compounds can be described as mixtures of Li₂S and MgS. As the molar percentage of Li₂S gradually increases and the molar percentage of MgS gradually decreases, the exhaustive method is used to determine the ternary compound compositions that can be formed by the above three ions: Li₂MgS₂, Li₄MgS₃, Li₆MgS₄, Li₈MgS₅, and Li₂MgS₅. 10 MgS6 (5 types of materials) conforms to composition space dimensionality reduction (reduced from two degrees of freedom to one degree of freedom).
[0062] After the composition of the Li-Mg-S ternary solid-state electrolyte system was determined, crystal structure prediction methods were used to predict the crystal structures of the above five materials at 1x, 2x, and 4x unit cells. The lowest energy among the three was taken as the predicted crystal structure. The results are as follows: Figure 5 As shown. Figure 5 The predicted crystal structure of the Li-Mg-S ternary solid electrolyte system in Example 3 is shown. Figure 5 The leftmost part shows the MgS crystal structure, and the rightmost part shows the Li2S crystal structure. From left to right, it shows the gradual transition from MgS to Li2S. It can be clearly observed that the MgS content gradually decreases and the Li2S content gradually increases.
[0063] This embodiment calculates the Energy above hull for the five predicted crystal structures. The calculations show that the Energy above hull for all five predicted crystal structures is less than 50 meV / atom, indicating their thermodynamic stability.
[0064] This embodiment uses the Pymatgen Python library for phase diagram analysis and electrochemical window analysis to calculate the electrochemical windows for the five predicted crystal structures. The calculations show that the electrochemical windows for these five predicted crystal structures are similar to those of traditional S-based solid electrolytes (Li). 10 GeP2S 12 )quite.
[0065] This embodiment systematically studies the Li diffusion performance of the above five predicted crystal structures. Li diffusion performance needs to be examined from two aspects: vacancy diffusion and interstitial diffusion. For vacancy diffusion, the location of the most stable Li vacancy should first be determined. Using crystal symmetry analysis, the number of equivalent Li types in the above five predicted crystal structures is calculated. The number of equivalent Li types in Li₂MgS₂ is 1, so the vacancy obtained by removing any Li atom is the most stable vacancy; the number of equivalent Li types in Li₄MgS₃, Li₆MgS₄, and Li₈MgS₅ is 2; Li 10 The number of equivalent Li species for MgS6 is 6. Therefore, Li4MgS3, Li6MgS4, Li8MgS5, and Li 10 For the four MgS6 materials, the location of the most stable Li vacancy needs to be determined by calculating the Li vacancy formation energy. After obtaining the most stable Li vacancy, the next step is to determine the Li vacancy diffusion path that is meaningful for evaluation. For any of the above predicted crystal structures, the distance between the most stable Li vacancy and the surrounding Li atoms is calculated and arranged in ascending order. Paths with excessively large distances are excluded using a 5 Å threshold. For paths with distances less than 5 Å, it is determined whether they can diffuse over long distances, and paths that cannot diffuse over long distances are further excluded. For paths that can diffuse over long distances and whose diffusion distance is less than 5 Å, the IDPP method is used to construct the initial path for the damped elastic band simulation, and VASP software is used as the simulation software for the damped elastic band method to evaluate the path energy barrier.
[0066] For interstitial diffusion, similarly, the location of the most stable Li interstitial atom should first be determined. To this end, a 24×24×24 three-dimensional grid was constructed in the five predicted crystal structures mentioned above. A test atom was placed at each grid point. If the distance between the test atom and all existing atoms in the predicted crystal structure is greater than 1.5 Å, it indicates that placing a Li interstitial atom at that point will not overlap with the existing atoms, making it a potential location for a Li interstitial atom. Since there are too many potential Li interstitial atoms, and many of them are symmetrically equivalent, a crystal symmetry analysis method was used to group the equivalent Li interstitial atoms, retaining only one representative from each group. The interstitial formation energy of these representative Li interstitial atoms was calculated; the lowest energy corresponds to the most stable Li interstitial atom. Using this location as the initial position, an unobstructed direction in the crystal was selected, and the adjacent sites in this direction were used as the final positions to form potential diffusion paths. The IDPP method was used to construct the initial path for damped elastic band simulation, and VASP software was used as the simulation software for the damped elastic band method to evaluate the path energy barrier. Figure 6 As shown. Figure 6 The Li diffusion performance of the Li-Mg-S ternary solid electrolyte in Example 2 shows that its diffusion barrier is approximately 0.30 eV, indicating its potential as a solid electrolyte.
[0067] As can be seen from the above embodiments, this invention, based on the fact that elements in solid electrolytes often appear in their common valence states, reduces the degree of freedom of the ternary composition space to one dimension, greatly narrowing the research scope of novel solid electrolytes. Based on this reduced composition space, this invention constructs an automated process for crystal structure prediction, achieving the analysis of the ground-state crystal structure. Finally, this invention proposes a method for systematically studying the diffusion barrier of a material, enabling accurate determination of its alkali metal (Li) ion diffusion performance. Based on the above process, this invention has discovered solid electrolyte materials with extremely low Li ion diffusion barriers in both the Li-Ag-X and Li-Mg-X ternary systems. This invention provides important theoretical tools and practical materials for the exploration of solid electrolyte systems in all-solid-state batteries.
[0068] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for screening ternary alkali metal solid electrolytes, characterized in that, Includes the following steps: (1) Determine the oxidation states of the three elements in the ternary alkali metal solid electrolyte based on their electronegativity, and determine the two binary compounds that constitute the ternary alkali metal solid electrolyte based on their oxidation states. (2) Based on the molar percentage of any binary compound in step (1) from low to high or from high to low, use the exhaustive method to obtain a series of ternary compound components that can be formed by the three elements in the ternary alkali metal solid electrolyte; (3) The crystal structure prediction method is used to predict the crystal structure of the 1-cell, 2-cell and 4-cell of a series of ternary compound components in step (2). The predicted structure with the lowest unit atomic energy among the three types of cells is taken as the predicted crystal structure of a series of ternary compound components. (4) Calculate the superconvex hull energy of the predicted crystal structure of a series of ternary compound components obtained in step (3), and screen to obtain the thermodynamically stable predicted crystal structure. (5) Perform electrochemical window analysis on the thermodynamically stable predicted crystal structure obtained in step (4) to screen out electrochemically stable ternary alkali metal solid electrolyte materials. (6) The electrochemically stable ternary alkali metal solid electrolyte material obtained in step (5) is subjected to alkali metal diffusion performance test to obtain the diffusion barrier of alkali metal, and ternary alkali metal solid electrolyte with low diffusion barrier is screened; the diffusion performance includes vacancy diffusion and interstitial diffusion. The diffusion barrier includes a vacancy diffusion barrier and a gap diffusion barrier; the diffusion performance test includes constructing a damped elastic band to simulate the initial path, and then using the damped elastic band method to evaluate the vacancy diffusion barrier and the gap diffusion barrier.
2. The screening method for ternary alkali metal solid electrolytes according to claim 1, characterized in that, In step (1), when the electronegativity of an element is ≥2.4, its oxidation state is negative; when the electronegativity of an element is <2.4, its oxidation state is positive.
3. The screening method for ternary alkali metal solid electrolytes according to claim 1, characterized in that, In step (4), when the superconvex hull energy per unit atom is < 50 meV, a thermodynamically stable predicted crystal structure is obtained by screening.
4. The screening method for ternary alkali metal solid electrolytes according to claim 1, characterized in that, In step (3), the crystal structure prediction method is performed using crystal structure prediction software, namely CALYPSO; in step (5), the electrochemical window analysis is performed using the Pymatgen Python library; in step (6), the initial path of the damping elastic band simulation is constructed using the IDPP method, and the damping elastic band method uses VASP software as the computational simulation software.
5. The screening method for ternary alkali metal solid electrolytes according to claim 1 or 4, characterized in that, The vacancy diffusion test includes the following steps: using the crystal symmetry analysis method, calculate the number of equivalent alkali metal atoms in the unit cell of the electrochemically stable ternary alkali metal solid electrolyte material obtained in step (5), and obtain the number of vacancies in the unit cell; calculate the vacancy formation energy of each type of vacancy, screen the vacancy with the lowest vacancy formation energy as the most stable vacancy in the unit cell, take the most stable vacancy in the unit cell as the center, calculate the distance from it to each equivalent alkali metal atom, use 5 Å as the threshold, exclude diffusion paths with a distance ≥ 5 Å, for diffusion paths with a distance less than 5 Å, determine whether it can diffuse over a long distance, for paths that can diffuse over a long distance and have a distance less than 5 Å, construct a damped elastic band to simulate the initial path, and then use the damped elastic band method to evaluate the vacancy diffusion energy barrier.
6. The screening method for ternary alkali metal solid electrolytes according to claim 1 or 4, characterized in that, The interstitial diffusion test includes the following steps: a three-dimensional grid is constructed in the unit cell of the electrochemically stable ternary alkali metal solid electrolyte material obtained in step (5), and alkali metal test atoms are placed at each grid point. When the distance between the alkali metal test atoms and the original atoms in the crystal structure of the electrochemically stable ternary alkali metal solid electrolyte material is greater than 1.5 Å, the potential position of the alkali metal interstitial atom is obtained; using the crystal symmetry analysis method, the equivalent alkali metal interstitial atoms at the potential positions of the alkali metal interstitial atoms are grouped, and only one is retained in each group as a representative alkali metal interstitial atom; the interstitial formation energy of the representative alkali metal interstitial atom is calculated, and the one with the lowest energy is the most stable alkali metal interstitial atom. The most stable alkali metal interstitial atom is taken as the initial position, and the equivalent adjacent site in the unobstructed direction in the crystal is taken as the final position to form a potential diffusion path. A damped elastic band is constructed to simulate the initial path, and then the damped elastic band method is used to evaluate the interstitial diffusion energy barrier.
7. The screening method for ternary alkali metal solid electrolytes according to claim 1, characterized in that, The elemental composition of the ternary alkali metal solid electrolyte includes Li-Ag-X or Li-Mg-X, where X is O, S or Cl.
8. The screening method for ternary alkali metal solid electrolytes according to claim 1 or 7, characterized in that, The ternary alkali metal solid electrolytes obtained through screening include LiAg5S3, LiAg3S2, Li2Ag4S3, LiAgS, Li4Ag2S3, Li3AgS2, Li5AgS3, LiAg5O3, LiAg3O2, Li2Ag4O3, LiAgO, Li4Ag2O3, Li3AgO2, Li5AgO3, Li2MgS2, Li4MgS3, Li6MgS4, Li8MgS5, and Li 10 MgS6.
9. A screening system for ternary alkali metal solid electrolytes, characterized in that, include: The dimensionality reduction module for the composition space of ternary alkali metal solid electrolytes is used to determine the two binary compounds that constitute the ternary solid electrolyte based on the electronegativity of the three elements that make up the ternary solid electrolyte. The module uses an exhaustive method to generate a series of candidate components of ternary solid electrolytes with different compositions that can be formed by the three elements in the ternary alkali metal solid electrolyte from the two binary compounds, thereby achieving dimensionality reduction of the composition space. An automated structure prediction module is connected to the ternary alkali metal solid electrolyte component spatial dimensionality reduction module to receive each ternary solid electrolyte candidate component, and to perform crystal structure prediction and total crystal energy calculation for each candidate component at 1x, 2x, and 4x unit cells, and to screen out the optimal crystal structure with the lowest energy for each candidate component. The crystal performance screening module is connected to the automated structure prediction module to receive the optimal crystal structure of each candidate component, screen out thermodynamically stable candidate materials with a superconvex hull energy per atom <50 meV through phase diagram analysis, and then perform electrochemical window analysis on the thermodynamically stable candidate materials to screen out electrochemically stable candidate materials. An alkali metal ion diffusion performance measurement module is connected to the crystal performance screening module to receive electrochemically stable candidate materials, test the alkali metal vacancy diffusion performance and alkali metal interstitial diffusion performance of the electrochemically stable candidate materials, and screen out ternary alkali metal solid electrolytes with low diffusion barriers based on the diffusion energy barrier of alkali metals.
10. A computer-storable medium, characterized in that, The computer storage medium is used to perform the screening method for ternary alkali metal solid electrolytes as described in any one of claims 1 to 8.